Traditional Medicine in Peru: In vitro antimicrobial activity of essential extracted oils from some aromatic plants - Alzamora, Libertad (2001)
The objective was to investigate the antimicrobial qualitative activities of five plants used in Traditional Medicine in Peru: Eucalyptus globulus, Labill "eucaliptus"; Cymbopogon citratus, (D.C.) Staff "hierba luisa"; Tagetes pusilla, Lag "anis serrano"; Senecio tephrosioides, Turcz "huamanrripa" y Lepechinia meyenii, (Walp) Epling "salvia". The essential oils were prepared by steam distillation and tested against Salmonella typhi ATCC 6539, S. typhimurium ATCC 14028, S. enteritidis INS, Vibrio cholerae ATCC E-7946 OGAWA, Pseudomonas aeruginosa GT 28, Shigella flexneri INS, Staphylococcus aureus INS, S. aureus ATCC 6538P and Candida albicans ATCC 10231. Test was controlled with antibiotic discs. Essential oils showed diverse effects against both Gram positive and Gram negative microorganisms. None of these inhibited the growth of Pseudomonas aeruginosa.